Riverine and glacier influence on infaunal benthic communities in Isfjorden, Svalbard. - Ugelstad, Charlotte Pedersen (UiT Norges arktiske universitet, 2019)
Fjords are the interface between land and ocean, and processes happening on land have implication for the coastal areas. In addition, differences in fjord characteristics, such as morphology, sedimentation and water circulation, can drive differences in fjord ecology, including benthic community composition (Syvitsky et al. 1986). Soft-bottom macro-fauna was collected in August 2018 using a Van-Veen grab along inner to outer fjord transects in Billefjord, Tempelfjord and Adventfjord, as well as several nearshore river estuaries, nearshore glacier sites and shallow control stations. Samples were collected from 30 stations, and community composition was analyzed in relation to environmental factors, including temperature, redox potential (Eh), grain size, total organic matter, salinity bottom water and sediment chlorophyll a, and phaeopigment. Results from this study suggest that overarching fjord-based differences are overwhelmed by small-scale drivers with more local impacts, in terms of benthic community structure. Different environmental characteristics were observed between sampled habitats, with regards to chlorophyll a, phaeopigments, sediment porosity and temperature. Eight significant clusters were identified according to community data, and the majority of these clusters clustered according to habitat type. Species richness increase towards less disturbed environment, as well as difference in dominating taxa varied between clusters. Indicating that shallow areas are more temporally unstable, whilst the deeper areas are more stable. Benthic communities contribute to several key biogeochemical processes in sediments, re-mineralization of nutrients, as well as act as a food source for higher tropical levels. Therefore, the purpose with this study was to highlight these coastal areas and investigate how the different benthic communities differs between habitats and how different environmental drivers influence the benthic community structure. Keywords: Benthic community, Coastal environment, Fjord system, ...